Breathable composite fabric and preparation process thereof
By using the interweaving technology of cotton fiber and bamboo charcoal fiber and the composite crochet of polyester fiber in automotive interior fabrics, combined with plasma treatment and padding treatment, the existing fabrics have poor moisture-conducting and breathable properties, limited antibacterial effects and insufficient flame retardant durability, and fabric preparation with high breathability, antibacterial properties and flame retardant durability are achieved.
Patent Information
- Application Number
- CN202510013305.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
AI Technical Summary
The moisture-guided and breathable properties of existing car interior fabrics are not ideal, the stuffy environment reduces driving comfort, limited antibacterial effect, and insufficient flame retardant and durability, which affects driving safety.
The blend of cotton fiber and bamboo charcoal fiber is used as warp threads, the cotton fiber is interwoven as weft threads to form a base cloth, the bamboo charcoal fiber and polyester fiber interwoven to form a reinforcement layer, the fabric body is formed through polyester fiber composite crochet, and plasma treatment and padding are carried out. The protective finishing liquid is prepared using modified cellulose nanocrystals, composite gelatin and other materials.
It improves the breathability, antibacteriality and flame retardant durability of the fabric, enhances the comfort and deformation resistance of the fabric, and meets the needs of green and environmentally friendly, high flame retardant, high antibacterial and water resistance.
Smart Images

Figure BDA0005229069780000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fabrics, in particular to a breathable composite fabric and a preparation process thereof. Background Art
[0002] With the rapid development of the automobile industry, the production and manufacturing requirements of automobiles are continuously increasing. Consumers' requirements for automobile interior decoration are also developing towards functionality and diversification, and the requirements for various fabric base fabrics used for automobile interior decoration are also diversified.
[0003] Existing automobile interiors are mostly made of polyester fabrics, but the moisture conductivity and breathability of polyester fabrics are not ideal. The stuffy environment will reduce the comfort of the driver and passengers, and the antibacterial effect is limited. Long-term use will easily breed bacteria and produce odor. At the same time, there are deficiencies in flame retardancy, durability, safety and environmental protection, which is not conducive to the safety protection of the driver and passengers. Summary of the invention
[0004] The purpose of the present invention is to provide a breathable composite fabric and a preparation process thereof to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A preparation process of a breathable composite fabric comprises the following steps:
[0007] S1: blending cotton fiber and bamboo charcoal fiber as warp, using cotton fiber as weft, interweaving the warp and weft to form a base fabric; interweaving bamboo charcoal fiber and polyester fiber to obtain a reinforcement layer; and compositely weaving the base fabric and the reinforcement layer with polyester fiber to obtain a fabric body;
[0008] S2: Plasma treatment is performed on the fabric body to obtain a pre-treated fabric body;
[0009] S3: preparing protective finishing liquid using modified cellulose nanocrystals, composite gelatin, N-carboxyethyl chitosan, acrylic acid, octadecyl methacrylate, N-(hydroxymethyl)acrylamide, vinyl-terminated polydimethylsiloxane, emulsifier, initiator, and deionized water;
[0010] S4: transferring the pretreated fabric body to a protective finishing liquid, performing a padding treatment, and then drying to obtain a breathable composite fabric.
[0011] Furthermore, in the preparation of the base fabric, the blending ratio of cotton fiber and bamboo charcoal fiber in the warp is 50:50; and the mass ratio of bamboo charcoal fiber to polyester fiber in the reinforcement layer is 1:2.
[0012] Furthermore, the working conditions of the plasma treatment are: in an argon environment, the power is 80 W, the discharge voltage is 220 Pa, and the time is 30 s.
[0013] Furthermore, the protective finishing liquid is composed of: deionized water as solvent, modified cellulose nanocrystals (2-4) g / L, composite gelatin 8 g / L, N-carboxyethyl chitosan 6 g / L, acrylic acid 4 g / L, methacrylate octadecyl ester 5 g / L, N-(hydroxymethyl) acrylamide 4 g / L, vinyl-terminated polydimethylsiloxane 2 g / L, initiator 0.7 g / L, and emulsifier 1.3 g / L.
[0014] Furthermore, the working conditions of the padding treatment are: a two-dip and two-pad process, a dipping time of 90-110 seconds, a padding ratio of 85%, keeping the temperature at 85°C for 5 minutes, and heating to 120°C for 8 minutes.
[0015] Further, the preparation of N-carboxyethyl chitosan comprises the following steps:
[0016] Chitosan, acrylic acid and deionized water were mixed, heated to 48-52°C and kept warm for 11-12 hours, cooled, added with acetone, washed with acetone for 2-3 times, and dried to obtain N-carboxyethyl chitosan.
[0017] Further, the preparation of modified cellulose nanocrystals comprises the following steps:
[0018] (1) Mixing cellulose nanocrystals and deionized water, ultrasonically dispersing for 20-30 minutes, adding anhydrous ethanol and zinc acetate, ultrasonically treating for 15-20 minutes, heating to 68-72° C. and keeping warm for 20-40 minutes, adjusting the pH value to 7, and keeping warm for 3-4 hours, transferring to an oil bath at 118-122° C. and keeping warm for 30-40 minutes, cooling, centrifuging, and freeze-drying to obtain composite cellulose nanocrystals;
[0019] (2) mixing the composite cellulose nanocrystals and Tris-HCl buffer, ultrasonically treating for 10-20 min, adding a mixture of dopamine hydrochloride and Tris-HCl buffer, ultrasonically treating for 10-15 min, placing in a 20-25° C. water bath, stirring for 10-12 h, centrifuging, freeze-drying, and grinding to obtain polydopamine-coated composite cellulose nanocrystals;
[0020] (3) The polydopamine-coated composite cellulose nanocrystals, hexaboron phosphazene, and Tris-HCl buffer were mixed, ultrasonically stirred for 1-2 hours, and heated to 35-40° C. for 1-2 hours to obtain modified cellulose nanocrystals.
[0021] Further, the preparation of the composite gelatin comprises the following steps:
[0022] 1) Under a nitrogen atmosphere, vanillin, pyridine and dichloromethane are mixed, a mixed solution of methacryloyl chloride and dichloromethane is added, the temperature is raised to 36-40° C. and the mixture is kept warm for 3-4 hours, rotary evaporated, ethyl acetate is added, and the mixture is washed with a saturated aqueous sodium chloride solution, a saturated aqueous sodium bicarbonate solution and deionized water for 3-5 times in sequence, dried over anhydrous magnesium sulfate, rotary evaporated, ethanol is added, filtered and dried to obtain methacrylic vanillin ester;
[0023] 2) Mix deionized water, ethanol and gelatin, heat until dissolved, cool to 48-52°C, add vanillin methacrylate, keep warm for 1-2 hours, then add 2-methylpyridine-N-borane, keep warm for 12-14 hours, wash with ethanol 3-5 times, and dry to obtain an intermediate preparation;
[0024] 3) The intermediate preparation, PBS buffer and N,N-dimethylformamide are mixed, and a mixed solution of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N,N-dimethylformamide is added, the pH value is adjusted to 5, and the mixture is stirred for 20-30 minutes. A mixed solution of dopamine hydrochloride and PBS buffer is added, the temperature is raised to 58-62° C., and stirred for 9-10 hours in the dark. A mixed solution of hexaboron phosphazene and N,N-dimethylformamide is added, the temperature is raised to 35-40° C. and kept warm for 1-2 hours, rotary evaporated, dialyzed with deionized water for 2 days, and freeze-dried to obtain composite gelatin.
[0025] Furthermore, the mass ratio of the intermediate preparation, dopamine hydrochloride and hexaboron phosphazene is 1:2:0.6.
[0026] Furthermore, the preparation of hexaboron phosphazene includes the following steps: under a nitrogen atmosphere, hexachlorophosphazene and acetone are mixed, a mixed solution of boric acid and deionized water is added, the mixture is kept at 58-62° C. for 2-3 hours, and rotary evaporated to obtain hexaboron phosphazene.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a breathable composite fabric and a preparation process thereof. Polyester fiber is used to compositely weave a base fabric and a reinforcement layer to obtain a fabric body, which is then plasma treated and transferred to a protective finishing liquid for padding treatment to obtain a green, environmentally friendly, highly flame-retardant, highly antibacterial and water-resistant breathable composite fabric.
[0029] By using a blend of moisture-absorbing, perspiration-releasing, antibacterial and deodorizing bamboo charcoal fiber and cotton fiber as the warp, and cotton fiber as the weft, the warp and weft are interwoven to form a base cloth, thereby greatly improving the comfort of the fabric. In order to solve the problem of low strength of bamboo charcoal fiber, bamboo charcoal fiber is selected as the warp, and high-strength polyester fiber is selected as the weft, and the warp and weft are interwoven to form a reinforcement layer. The base cloth and the reinforcement layer are compositely crocheted with polyester fiber to obtain the fabric body, which greatly improves the fabric's resistance to deformation while ensuring the comfort of the fabric. Then, the fabric body is plasma treated to improve the bonding strength between the fabric body and the protective finishing liquid.
[0030] In order to meet the requirements of green production, the bio-based raw materials chitosan and gelatin are selected as the base materials of the protective finishing liquid in the present invention. In order to improve the solubility of chitosan, chitosan is modified with acrylic acid to obtain soluble N-carboxyethyl chitosan; cold water fish skin gelatin is selected as gelatin, and the gelatin is modified by quantitatively modifying vanillin methacrylate and dopamine, wherein vanillin methacrylate is prepared with vanillin and methacryloyl chloride as raw materials, thereby improving the adhesion and antibacterial properties of gelatin; grafting dopamine to introduce catechol groups into gelatin, which is beneficial to further improve the bonding strength between the modified gelatin and the fabric, and then the catechol groups on it are used to graft the flame retardant hexaboron phosphazene to obtain a composite gelatin with a dynamic borate ester bond, wherein hexaboron phosphazene is a halogen-free, environmentally friendly flame retardant synthesized from readily available raw materials boric acid and hexachlorophosphazene to synthesize PNB synergistic flame retardant, thereby giving the fabric lasting flame retardancy.
[0031] In order to give the composite fabric excellent antibacterial and breathable properties, zinc acetate is used as a zinc source and cellulose nanocrystals are used as templates. Composite cellulose nanocrystals with nano-zinc oxide uniformly dispersed on the surface of cellulose nanocrystals are obtained through in-situ polymerization-precipitation. In order to improve the uniformity of dispersion of the composite cellulose nanocrystals in a protective finishing liquid, the composite cellulose nanocrystals are modified and polymerized using dopamine to obtain polydopamine-wrapped composite cellulose nanocrystals. Then, the catechol groups on the surface of dopamine are used to graft hexaboron phosphazene to obtain modified cellulose nanocrystals with dynamic borate ester bonds, thereby greatly improving the flame retardancy and durability of the fabric.
[0032] In order to give breathable fabrics excellent water resistance, octadecyl methacrylate, N-(hydroxymethyl) acrylamide, and vinyl-terminated polydimethylsiloxane are introduced into the protective finishing liquid as waterproof ingredients. Under the action of initiators, they polymerize with acrylic acid and modified gelatin with double bonds to increase the complexity of the cross-linking network, greatly improve the bonding strength between the protective finishing liquid and the composite fabric, and give the composite fabric lasting flame retardancy, antibacterial and water resistance. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0035] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention and are not used to limit the present invention.
[0036] Embodiment 1: A process for preparing a breathable composite fabric, comprising the following steps:
[0037] S1: blending cotton fiber and bamboo charcoal fiber as warp and cotton fiber as weft, interweaving the warp and weft to form a base fabric; interweaving bamboo charcoal fiber and polyester fiber to obtain a reinforcement layer; and compositely weaving the base fabric and the reinforcement layer with polyester fiber to obtain a fabric body;
[0038] In the preparation of the base fabric, the blending ratio of cotton fiber and bamboo charcoal fiber in the warp is 50:50, the warp density is 400 strands / 10cm, and the weft density is 220 strands / 10cm; the mass ratio of bamboo charcoal fiber to polyester fiber in the reinforcement layer is 1:2;
[0039] S2: Plasma treatment is performed on the fabric body to obtain a pre-treated fabric body;
[0040] The working conditions of plasma treatment were: in an argon environment, the power was 80 W, the discharge voltage was 220 Pa, and the time was 30 s;
[0041] S3: preparing protective finishing liquid using modified cellulose nanocrystals, composite gelatin, N-carboxyethyl chitosan, acrylic acid, octadecyl methacrylate, N-(hydroxymethyl)acrylamide, vinyl-terminated polydimethylsiloxane, emulsifier, initiator, and deionized water;
[0042] Deionized water is used as solvent, wherein the modified cellulose nanocrystals are 2g / L, composite gelatin is 8g / L, N-carboxyethyl chitosan is 6g / L, acrylic acid is 4g / L, octadecyl methacrylate is 5g / L, N-(hydroxymethyl) acrylamide is 4g / L, vinyl-terminated polydimethylsiloxane is 2g / L, initiator is 0.7g / L, and emulsifier is 1.3g / L;
[0043] The preparation of N-carboxyethyl chitosan comprises the following steps:
[0044] Mix 2.5 g chitosan, 8 mL acrylic acid, and 130 mL deionized water, heat to 48 °C and keep warm for 12 h, cool, add 50 mL acetone, wash twice with acetone, and dry to obtain N-carboxyethyl chitosan;
[0045] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0046] (1) 2 g of cellulose nanocrystals and 98 mL of deionized water were mixed and ultrasonically dispersed for 20 min. 120 mL of anhydrous ethanol and 0.9 g of zinc acetate were added and ultrasonically treated for 15 min. The temperature was raised to 68 ° C and kept warm for 40 min. The pH value was adjusted to 7 and kept warm for 3 h. The mixture was transferred to an oil bath at 118 ° C and kept warm for 40 min. The mixture was cooled, centrifuged, and freeze-dried to obtain composite cellulose nanocrystals.
[0047] (2) Weigh 1.4 g of composite cellulose nanocrystals and 200 mL of Tris-HCl buffer, mix them, and ultrasonically treat them for 10 min. Add a mixture of 2.8 g of dopamine hydrochloride and 400 mL of Tris-HCl buffer, and ultrasonically treat them for 10 min. Place them in a 20°C water bath, stir them for 12 h, centrifuge, freeze-dry, and grind them to obtain polydopamine-coated composite cellulose nanocrystals.
[0048] (3) 2.4 g of polydopamine-coated composite cellulose nanocrystals, 0.9 g of hexaboron phosphazene, and 50 mL of Tris-HCl buffer were mixed, ultrasonically stirred for 1 h, and heated to 35 °C for 2 h to obtain modified cellulose nanocrystals;
[0049] The preparation of the composite gelatin comprises the following steps:
[0050] 1) Under a nitrogen atmosphere, 10 mmol vanillin, 12 mmol pyridine, and 20 mL dichloromethane were mixed, and a mixture of 12 mmol methacryloyl chloride and 5 mL dichloromethane was added, and the mixture was heated to 36°C and kept warm for 4 h, and then rotary evaporated, and 25 mL ethyl acetate was added. The mixture was washed three times with a saturated aqueous sodium chloride solution, a saturated aqueous sodium bicarbonate solution, and deionized water, and then dried over anhydrous magnesium sulfate, and rotary evaporated. 25 mL ethanol was added, and the mixture was filtered and dried to obtain methacrylic acid vanillate;
[0051] 2) 70 mL of deionized water, 30 mL of ethanol, and 15 g of gelatin were mixed, heated to dissolve, cooled to 48°C, 0.2 g of methacrylate vanillate was added, and the mixture was kept warm for 1 h, and then 0.07 g of 2-methylpyridine-N-borane was added, and the mixture was kept warm for 12 h, washed with ethanol three times, and dried to obtain an intermediate preparation;
[0052] 3) 1 g of the intermediate preparation, 9 mL of PBS buffer and 9 mL of N,N-dimethylformamide were mixed, and a mixture of 1.5 g of N-hydroxysuccinimide, 0.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (3-dimethylaminopropyl) and 4 mL of N,N-dimethylformamide was added, the pH value was adjusted to 5, stirred for 20 min, and a mixture of 2 g of dopamine hydrochloride and 2 mL of PBS buffer was added, the temperature was raised to 58 ° C, stirred for 10 h in the dark, and a mixed solution of 0.6 g of hexaboron phosphazene and 5 mL of N,N-dimethylformamide was added, the temperature was raised to 35 ° C and kept warm for 2 h, rotary evaporated, dialyzed with deionized water for 2 d, and freeze-dried to obtain composite gelatin;
[0053] The preparation of the hexaboron phosphazene comprises the following steps: in a nitrogen atmosphere, 1.7 g of hexachlorophosphazene and 25 mL of acetone are mixed, 1.8 g of boric acid and 25 mL of deionized water are added, the mixture is kept at 58° C. for 3 h, and rotary evaporated to obtain the hexaboron phosphazene;
[0054] S4: transferring the pretreated fabric body to the protective finishing liquid, performing padding treatment, and then drying to obtain a breathable composite fabric; the working conditions of the padding treatment are: adopting a two-dip and two-pad process, the dipping time is 90s, the padding rate is 85%, keeping warm at 85°C for 5min, heating to 120°C and keeping warm for 8min.
[0055] Embodiment 2: A process for preparing a breathable composite fabric, comprising the following steps:
[0056] S1: blending cotton fiber and bamboo charcoal fiber as warp and cotton fiber as weft, interweaving the warp and weft to form a base fabric; interweaving bamboo charcoal fiber and polyester fiber to obtain a reinforcement layer; and compositely weaving the base fabric and the reinforcement layer with polyester fiber to obtain a fabric body;
[0057] In the preparation of the base fabric, the blending ratio of cotton fiber and bamboo charcoal fiber in the warp is 50:50, the warp density is 400 strands / 10cm, and the weft density is 220 strands / 10cm; the mass ratio of bamboo charcoal fiber to polyester fiber in the reinforcement layer is 1:2;
[0058] S2: Plasma treatment is performed on the fabric body to obtain a pre-treated fabric body;
[0059] The working conditions of plasma treatment were: in an argon environment, the power was 80 W, the discharge voltage was 220 Pa, and the time was 30 s;
[0060] S3: preparing protective finishing liquid using modified cellulose nanocrystals, composite gelatin, N-carboxyethyl chitosan, acrylic acid, octadecyl methacrylate, N-(hydroxymethyl)acrylamide, vinyl-terminated polydimethylsiloxane, emulsifier, initiator, and deionized water;
[0061] Deionized water is used as solvent, wherein modified cellulose nanocrystals 3g / L, composite gelatin 8g / L, N-carboxyethyl chitosan 6g / L, acrylic acid 4g / L, octadecyl methacrylate 5g / L, N-(hydroxymethyl) acrylamide 4g / L, vinyl-terminated polydimethylsiloxane 2g / L, initiator 0.7g / L, emulsifier 1.3g / L;
[0062] The preparation of N-carboxyethyl chitosan comprises the following steps:
[0063] Mix 2.5 g chitosan, 8 mL acrylic acid, and 130 mL deionized water, heat to 50 °C and keep warm for 11.5 h, cool, add 50 mL acetone, wash twice with acetone, and dry to obtain N-carboxyethyl chitosan;
[0064] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0065] (1) 2 g of cellulose nanocrystals and 98 mL of deionized water were mixed and ultrasonically dispersed for 25 min. 120 mL of anhydrous ethanol and 0.9 g of zinc acetate were added and ultrasonically treated for 18 min. The temperature was raised to 70 °C and kept for 30 min. The pH value was adjusted to 7 and kept for 3.5 h. The mixture was transferred to an oil bath at 120 °C and kept for 35 min. The mixture was cooled, centrifuged, and freeze-dried to obtain composite cellulose nanocrystals.
[0066] (2) Weigh 1.4 g of composite cellulose nanocrystals and 200 mL of Tris-HCl buffer, mix them, and ultrasonically treat them for 15 min. Add a mixture of 2.8 g of dopamine hydrochloride and 400 mL of Tris-HCl buffer, and ultrasonically treat them for 13 min. Place them in a 22°C water bath, stir them for 11 h, centrifuge, freeze-dry, and grind them to obtain polydopamine-coated composite cellulose nanocrystals.
[0067] (3) 2.4 g of polydopamine-coated composite cellulose nanocrystals, 0.9 g of hexaboron phosphazene, and 50 mL of Tris-HCl buffer were mixed, ultrasonically stirred for 1.5 h, and heated to 38 °C for 1.5 h to obtain modified cellulose nanocrystals;
[0068] The preparation of the composite gelatin comprises the following steps:
[0069] 1) Under a nitrogen atmosphere, 10 mmol vanillin, 12 mmol pyridine, and 20 mL dichloromethane were mixed, and a mixture of 12 mmol methacryloyl chloride and 5 mL dichloromethane was added, and the temperature was raised to 38°C and kept warm for 3.5 h, and 25 mL ethyl acetate was added, and the mixture was washed with saturated aqueous sodium chloride solution, saturated aqueous sodium bicarbonate solution, and deionized water for 4 times in sequence, and dried over anhydrous magnesium sulfate, and 25 mL ethanol was added after filtration and drying to obtain methacrylic acid vanillate;
[0070] 2) 70 mL of deionized water, 30 mL of ethanol, and 15 g of gelatin were mixed, heated to dissolve, cooled to 50°C, 0.2 g of methacrylate vanillate was added, and the mixture was kept warm for 1.5 h, and then 0.07 g of 2-methylpyridine-N-borane was added, and the mixture was kept warm for 13 h. The mixture was washed with ethanol 4 times and dried to obtain an intermediate preparation;
[0071] 3) 1 g of the intermediate preparation, 9 mL of PBS buffer, and 9 mL of N,N-dimethylformamide were mixed, and a mixed solution of 1.5 g of N-hydroxysuccinimide, 0.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, and 4 mL of N,N-dimethylformamide was added, the pH value was adjusted to 5, and stirred for 25 min. A mixed solution of 2 g of dopamine hydrochloride and 2 mL of PBS buffer was added, and the temperature was raised to 60° C., and stirred in the dark for 9.5 h. A mixed solution of 0.6 g of hexaboron phosphazene and 5 mL of N,N-dimethylformamide was added, and the temperature was raised to 38° C. and kept warm for 1.5 h. The mixture was rotary evaporated, dialyzed with deionized water for 2 d, and freeze-dried to obtain composite gelatin;
[0072] The preparation of the hexaboron phosphazene comprises the following steps: under a nitrogen atmosphere, 1.7 g of hexachlorophosphazene and 25 mL of acetone are mixed, 1.8 g of boric acid and 25 mL of deionized water are added, the mixture is kept at 60° C. for 2.5 h, and rotary evaporated to obtain the hexaboron phosphazene;
[0073] S4: transferring the pretreated fabric body to the protective finishing liquid, performing a padding treatment, and then drying to obtain a breathable composite fabric; the working conditions of the padding treatment are: adopting a two-dip and two-pad process, the dipping time is 100s, the padding rate is 85%, keeping warm at 85°C for 5min, heating to 120°C and keeping warm for 8min.
[0074] Embodiment 3: A process for preparing a breathable composite fabric, comprising the following steps:
[0075] S1: blending cotton fiber and bamboo charcoal fiber as warp and cotton fiber as weft, interweaving the warp and weft to form a base fabric; interweaving bamboo charcoal fiber and polyester fiber to obtain a reinforcement layer; and compositely weaving the base fabric and the reinforcement layer with polyester fiber to obtain a fabric body;
[0076] In the preparation of the base fabric, the blending ratio of cotton fiber and bamboo charcoal fiber in the warp is 50:50, the warp density is 400 strands / 10cm, and the weft density is 220 strands / 10cm; the mass ratio of bamboo charcoal fiber to polyester fiber in the reinforcement layer is 1:2;
[0077] S2: Plasma treatment is performed on the fabric body to obtain a pre-treated fabric body;
[0078] The working conditions of plasma treatment were: in an argon environment, the power was 80 W, the discharge voltage was 220 Pa, and the time was 30 s;
[0079] S3: preparing protective finishing liquid using modified cellulose nanocrystals, composite gelatin, N-carboxyethyl chitosan, acrylic acid, octadecyl methacrylate, N-(hydroxymethyl)acrylamide, vinyl-terminated polydimethylsiloxane, emulsifier, initiator, and deionized water;
[0080] Deionized water is used as solvent, wherein the modified cellulose nanocrystals are 4g / L, composite gelatin is 8g / L, N-carboxyethyl chitosan is 6g / L, acrylic acid is 4g / L, octadecyl methacrylate is 5g / L, N-(hydroxymethyl) acrylamide is 4g / L, vinyl-terminated polydimethylsiloxane is 2g / L, initiator is 0.7g / L, and emulsifier is 1.3g / L;
[0081] The preparation of N-carboxyethyl chitosan comprises the following steps:
[0082] Mix 2.5 g chitosan, 8 mL acrylic acid, and 130 mL deionized water, heat to 52 °C and keep warm for 11 h, cool, add 50 mL acetone, wash with acetone three times, and dry to obtain N-carboxyethyl chitosan;
[0083] The preparation of the modified cellulose nanocrystals comprises the following steps:
[0084] (1) 2 g of cellulose nanocrystals and 98 mL of deionized water were mixed and ultrasonically dispersed for 30 min. 120 mL of anhydrous ethanol and 0.9 g of zinc acetate were added and ultrasonically treated for 20 min. The temperature was raised to 72 °C and kept warm for 20 min. The pH value was adjusted to 7 and kept warm for another 4 h. The mixture was transferred to an oil bath at 122 °C and kept warm for 30 min. The mixture was cooled, centrifuged, and freeze-dried to obtain composite cellulose nanocrystals.
[0085] (2) Weigh 1.4 g of composite cellulose nanocrystals and 200 mL of Tris-HCl buffer, mix them, and ultrasonically treat them for 20 min. Add a mixture of 2.8 g of dopamine hydrochloride and 400 mL of Tris-HCl buffer, and ultrasonically treat them for 15 min. Place them in a 25°C water bath, stir them for 10 h, centrifuge, freeze-dry, and grind them to obtain polydopamine-coated composite cellulose nanocrystals.
[0086] (3) 2.4 g of polydopamine-coated composite cellulose nanocrystals, 0.9 g of hexaboron phosphazene, and 50 mL of Tris-HCl buffer were mixed, ultrasonically stirred for 2 h, and heated to 40 °C for 1 h to obtain modified cellulose nanocrystals;
[0087] The preparation of the composite gelatin comprises the following steps:
[0088] 1) Under a nitrogen atmosphere, 10 mmol vanillin, 12 mmol pyridine, and 20 mL dichloromethane were mixed, and a mixture of 12 mmol methacryloyl chloride and 5 mL dichloromethane was added, and the mixture was heated to 40°C and kept warm for 3 h, and then rotary evaporated, and 25 mL ethyl acetate was added, and the mixture was washed with saturated aqueous sodium chloride solution, saturated aqueous sodium bicarbonate solution, and deionized water for 5 times in sequence, and then dried over anhydrous magnesium sulfate, and rotary evaporated, and 25 mL ethanol was added, and the mixture was filtered and dried to obtain methacrylic acid vanillate;
[0089] 2) 70 mL of deionized water, 30 mL of ethanol, and 15 g of gelatin were mixed, heated to dissolve, cooled to 52°C, 0.2 g of methacrylate vanillate was added, and the mixture was kept warm for 2 h, and then 0.07 g of 2-methylpyridine-N-borane was added, and the mixture was kept warm for 14 h. The mixture was washed with ethanol for 5 times and dried to obtain an intermediate preparation;
[0090] 3) 1 g of the intermediate preparation, 9 mL of PBS buffer and 9 mL of N,N-dimethylformamide were mixed, and a mixture of 1.5 g of N-hydroxysuccinimide, 0.9 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (3-dimethylaminopropyl) and 4 mL of N,N-dimethylformamide was added, the pH value was adjusted to 5, and stirred for 30 min, and a mixture of 2 g of dopamine hydrochloride and 2 mL of PBS buffer was added, and the mixture was heated to 62° C. and stirred for 10 h in the dark, and a mixed solution of 0.6 g of hexaboron phosphazene and 5 mL of N,N-dimethylformamide was added, and the mixture was heated to 40° C. and kept warm for 1 h, rotary evaporated, dialyzed with deionized water for 2 d, and freeze-dried to obtain composite gelatin;
[0091] The preparation of the hexaboron phosphazene comprises the following steps: under a nitrogen atmosphere, 1.7 g of hexachlorophosphazene and 25 mL of acetone are mixed, 1.8 g of boric acid and 25 mL of deionized water are added, the mixture is kept at 62° C. for 2 h, and rotary evaporated to obtain the hexaboron phosphazene;
[0092] S4: transferring the pretreated fabric body to the protective finishing liquid, performing padding treatment, and then drying to obtain a breathable composite fabric; the working conditions of the padding treatment are: adopting a two-dip and two-pad process, the dipping time is 110s, the padding rate is 85%, keeping warm at 85°C for 5min, heating to 120°C and keeping warm for 8min.
[0093] Comparative Example 1: Taking Example 3 as the control group, cellulose nanocrystals were used to replace the modified cellulose nanocrystals, and other processes were normal.
[0094] Comparative Example 2: Using Example 3 as the control group, gelatin was used to replace the composite gelatin, and other processes were normal.
[0095] Source of raw materials (for demonstration only):
[0096] Cotton fiber (16 count): Jiangsu Daai Textile Co., Ltd.; Bamboo charcoal fiber 75D / 72F: Zhejiang Datong Light Textile Co., Ltd.; Gelatin (cold water fish gelatin, G7041): Shanghai Beinuo Biotechnology Co., Ltd.; Emulsifier NP-10: Shandong Yukang Chemical Co., Ltd.; Polyester fiber DTY75D / 72F: Zhejiang Jinxia New Material Technology Co., Ltd.; Cellulose nanocrystal: (Kramer) Shanghai Puzhen Biotechnology Co., Ltd.; Vinyl-terminated polydimethylsiloxane (99%): Hubei Shixing Chemical Co., Ltd.; Acrylic acid A103526, octadecyl methacrylate S107562, N-(hydroxymethyl) acrylamide N492407, initiator (azobisisobutyronitrile) A434183, chitosan C434554, Zinc acetate Z111245, Tris-HCl buffer T301502, dopamine hydrochloride D103111, vanillin V100115, pyridine P111511, methacryloyl chloride M109517, 2-methylpyridine-N-borane P122349, PBS buffer B478425, N,N-dimethylformamide D111999, N-hydroxysuccinimide H109330, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride E106172, hexachlorophosphazene P107062, boric acid B111592: Aladdin reagent; sodium hydroxide, anhydrous ethanol, dichloromethane, ethyl acetate, sodium chloride, sodium bicarbonate, anhydrous magnesium sulfate, acetone, analytical grade: Sinopharm reagent.
[0097] Performance test: The composite fabrics prepared in the embodiments and comparative examples were tested for performance:
[0098] Air permeability: Refer to GB / T5453, test area is 50cm 2, the pressure difference of the sample is 127Pa, the test temperature is 25℃, and the air permeability is detected; antibacterial durability: the sample is tested after 30 standard washes, the Gram-positive bacteria Staphylococcus aureus is used, and the antibacterial property is detected with reference to GB / T20944.3-2008; flame retardant durability: the sample is tested after 30 standard washes, and the warp horizontal burning speed (mm / min) is graded with reference to GB / T8410, and the result is characterized as follows: the sample is in the flame for 15s, and after the fire source is extinguished, it does not burn or burns but extinguishes before the first mark (38mm), and the result is characterized as A-0; the flame extinguishes itself within 60s, and the burning distance is not more than 50mm, and the result is characterized as B. The test results are shown in Table 1;
[0099] Table 1
[0100]
[0101] The present invention provides a breathable composite fabric and a preparation process thereof. Polyester fiber is used to compositely weave a base fabric and a reinforcement layer to obtain a fabric body, which is then plasma treated and transferred to a protective finishing liquid for padding treatment to obtain a green, environmentally friendly, highly flame-retardant, highly antibacterial and water-resistant breathable composite fabric.
[0102] Example 3 is compared with Comparative Example 1. In order to give the composite fabric excellent antibacterial properties and air permeability, zinc acetate is used as a zinc source and cellulose nanocrystals are used as templates. Composite cellulose nanocrystals with nano-zinc oxide uniformly dispersed on the surface of cellulose nanocrystals are obtained by in-situ polymerization-precipitation. In order to improve the uniformity of dispersion of the composite cellulose nanocrystals in the protective finishing liquid, the composite cellulose nanocrystals are modified and polymerized by dopamine to obtain polydopamine-wrapped composite cellulose nanocrystals, and then the catechol group on the surface of dopamine is used to graft hexaboron phosphazene to obtain modified cellulose nanocrystals with dynamic borate ester bonds, thereby greatly improving the flame retardancy and durability of the fabric.
[0103] Example 3 is compared with Comparative Example 2. In order to meet the requirements of green production, bio-based raw materials chitosan and gelatin are selected as the base materials of the protective finishing liquid in the present invention. In order to improve the solubility of chitosan, chitosan is modified with acrylic acid to obtain soluble N-carboxyethyl chitosan; cold water fish skin gelatin is selected as gelatin, and the gelatin is modified by quantitatively modifying vanillin methacrylate and dopamine, wherein vanillin methacrylate is prepared from vanillin and methacryloyl chloride as raw materials, thereby improving the adhesion and antibacterial properties of gelatin; grafting dopamine to introduce catechol groups into gelatin, which is beneficial to further improve the bonding strength between the modified gelatin and the fabric, and then the catechol groups thereon are used to graft the flame retardant hexaboron phosphazene to obtain a composite gelatin with a dynamic borate ester bond, wherein hexaboron phosphazene is a halogen-free, environmentally friendly flame retardant synthesized from readily available raw materials boric acid and hexachlorophosphazene to synthesize PNB for synergistic flame retardancy, thereby giving the fabric a long-lasting flame retardancy.
[0104] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A process for preparing a breathable composite fabric, characterized in that: The steps include: S1: blending cotton fiber and bamboo charcoal fiber as warp, using cotton fiber as weft, interweaving the warp and weft to form a base fabric; interweaving bamboo charcoal fiber and polyester fiber to obtain a reinforcement layer; and compositely weaving the base fabric and the reinforcement layer with polyester fiber to obtain a fabric body; S2: Plasma treatment is performed on the fabric body to obtain a pre-treated fabric body; S3: preparing protective finishing liquid using modified cellulose nanocrystals, composite gelatin, N-carboxyethyl chitosan, acrylic acid, octadecyl methacrylate, N-(hydroxymethyl)acrylamide, vinyl-terminated polydimethylsiloxane, emulsifier, initiator, and deionized water; S4: transferring the pretreated fabric body to a protective finishing liquid, performing a padding treatment, and then drying to obtain a breathable composite fabric.
2. The process for preparing a breathable composite fabric according to claim 1, characterized in that: In the preparation of the base fabric, the blending ratio of cotton fiber and bamboo charcoal fiber in the warp is 50:50; the mass ratio of bamboo charcoal fiber to polyester fiber in the reinforcement layer is 1:
2.
3. The process for preparing a breathable composite fabric according to claim 1, characterized in that: The working conditions of plasma treatment are: in an argon environment, the power is 80 W, the discharge voltage is 220 Pa, and the time is 30 s.
4. The process for preparing a breathable composite fabric according to claim 1, characterized in that: The protective finishing liquid is composed of: deionized water as solvent, modified cellulose nanocrystals (2-4) g / L, composite gelatin 8 g / L, N-carboxyethyl chitosan 6 g / L, acrylic acid 4 g / L, methacrylate octadecyl ester 5 g / L, N-(hydroxymethyl) acrylamide 4 g / L, vinyl-terminated polydimethylsiloxane 2 g / L, initiator 0.7 g / L, and emulsifier 1.3 g / L.
5. The process for preparing a breathable composite fabric according to claim 1, characterized in that: The working conditions of the padding treatment are: two-dip and two-rolling process, the dipping time is 90-110s, the rolling ratio is 85%, the temperature is kept at 85°C for 5min, and the temperature is increased to 120°C and kept for 8min.
6. The process for preparing a breathable composite fabric according to claim 1, characterized in that: The preparation of the modified cellulose nanocrystals comprises the following steps: (1) Mixing cellulose nanocrystals and deionized water, ultrasonically dispersing for 20-30 minutes, adding anhydrous ethanol and zinc acetate, ultrasonically treating for 15-20 minutes, heating to 68-72° C. and keeping warm for 20-40 minutes, adjusting the pH value to 7, and keeping warm for 3-4 hours, transferring to an oil bath at 118-122° C. and keeping warm for 30-40 minutes, cooling, centrifuging, and freeze-drying to obtain composite cellulose nanocrystals; (2) mixing the composite cellulose nanocrystals and Tris-HCl buffer, ultrasonically treating for 10-20 min, adding a mixture of dopamine hydrochloride and Tris-HCl buffer, ultrasonically treating for 10-15 min, placing in a 20-25° C. water bath, stirring for 10-12 h, centrifuging, freeze-drying, and grinding to obtain polydopamine-coated composite cellulose nanocrystals; (3) The polydopamine-coated composite cellulose nanocrystals, hexaboron phosphazene, and Tris-HCl buffer were mixed, ultrasonically stirred for 1-2 hours, and heated to 35-40° C. for 1-2 hours to obtain modified cellulose nanocrystals.
7. The process for preparing a breathable composite fabric according to claim 1, characterized in that: The preparation of the composite gelatin comprises the following steps: 1) Under a nitrogen atmosphere, vanillin, pyridine and dichloromethane are mixed, a mixed solution of methacryloyl chloride and dichloromethane is added, the temperature is raised to 36-40° C. and the mixture is kept warm for 3-4 hours, rotary evaporated, ethyl acetate is added, and the mixture is washed with a saturated aqueous sodium chloride solution, a saturated aqueous sodium bicarbonate solution and deionized water for 3-5 times in sequence, dried over anhydrous magnesium sulfate, rotary evaporated, ethanol is added, filtered and dried to obtain methacrylic vanillin ester; 2) Mix deionized water, ethanol and gelatin, heat until dissolved, cool to 48-52°C, add vanillin methacrylate, keep warm for 1-2 hours, then add 2-methylpyridine-N-borane, keep warm for 12-14 hours, wash with ethanol 3-5 times, and dry to obtain an intermediate preparation; 3) The intermediate preparation, PBS buffer and N,N-dimethylformamide are mixed, and a mixed solution of N-hydroxysuccinimide, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and N,N-dimethylformamide is added, the pH value is adjusted to 5, and the mixture is stirred for 20-30 minutes. A mixed solution of dopamine hydrochloride and PBS buffer is added, the temperature is raised to 58-62° C., and stirred for 9-10 hours in the dark. A mixed solution of hexaboron phosphazene and N,N-dimethylformamide is added, the temperature is raised to 35-40° C. and kept warm for 1-2 hours, rotary evaporated, dialyzed with deionized water for 2 days, and freeze-dried to obtain composite gelatin.
8. The process for preparing a breathable composite fabric according to claim 7, characterized in that: The mass ratio of the intermediate preparation, dopamine hydrochloride and hexaboron phosphazene is 1:2:0.
6.
9. A process for preparing a breathable composite fabric according to claim 6 or 7, characterized in that: The preparation of the hexaboron phosphazene comprises the following steps: under a nitrogen atmosphere, mixing hexachlorophosphazene and acetone, adding a mixed solution of boric acid and deionized water, keeping the mixture at 58-62° C. for 2-3 hours, and rotary evaporating to obtain the hexaboron phosphazene.
10. A breathable composite fabric, characterized in that: The invention is prepared by the preparation process according to any one of claims 1 to 8.
Citation Information
Cited By
Strong-sunscreen, high-air-permeability, moisture-absorption and quick-drying wrinkled fabric and preparation method thereof
CN120759101A